Empirical model for prediction of density and water resistance of corn cob briquettes. (2nd August 2019) - Jekayinfa, S.O.; Pecenka, Ralf; Orisaleye, J.I.
Biomass obtained from agricultural wastes have a high potential for energy generation, particularly in developing countries. The poor properties of the agricultural biomass cause handling problems and limit the suitability as fuel in conventional grates. Densification of biomass into briquettes enhances its fuel properties. In this study, effects of pressure (9, 15 MPa), temperature (90, 120°C), hold time (7.5, 15 minutes) and particle size (< 2.5 mm, > 2.5 mm) on physical properties of corn cob briquettes were investigated using a 2-level full factorial experimental design. A laboratory scale uniaxial briquetting press was used for densification of the milled corn cobs.The properties of briquettes considered are the density, which ranges from 578 to 1, 272 kg/m 3, and water resistance, which ranges from 32.7 to 94.8%. The empirical models developed for density and water resistance had coefficient of multiple determination for prediction of 80.42% and 95.82% respectively. The significant factors for density of the briquettes were pressure, temperature and particle size. The temperature and particle size along with their interaction was significant in determination of the water resistance. The empirical models predicted experimental data closely.